Pelatihan Penyusunan Laporan Keuangan Bagi UMKM di Gampong Blang Pulo - Hilmy Hilmi; Ilham Dy Satria; Sapna Biby (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this service activity is to find solutions to problems faced by UMKM business partners that the PKM implementation team runs in community service programs, through mentoring, and training. The method or approach that is offered and has been mutually agreed with UMKM business partners is training and mentoring as well as assistance in adding business raw materials to motivate partners in achieving business success. The results of PKM activities where Partners are very enthusiastic about participating in the training, this can be seen from the participants who attended the event from beginning to end and were very enthusiastic in question and answer sessions, discussions or sharing knowledge and about the products they produce. Based on the results of the evaluation, the participants were able to improve their understanding of making financial statement records for the UMKM businesses they run, and have begun to separate their UMKM business financial reports from family financial reports. On the other hand, product marketing has begun to increase, helped by promotions carried out through social media.